The Influence of the Bowl Championship Series on Competitive Balance in College Football - Stephen W. Dittmore; Craig M. Crow (Journal of Applied Sports Management, 2010)
Competitive balance in sport has been identified as a predictor of demand for sporting events, and leagues. Conferences frequently seek to maximize outcome uncertainty as a means of increasing demand. While competitive balance was not initially a goal of the Bowl Championship Series (BCS), competitive balance in American college football has generally been regarded as improved since the implementation of the BCS. The present study confirms empirically that within-season competitive balance inside all six founding BCS conferences has improved since its creation. However, only three of the six conferences exhibited improved between-season competitive balance, meaning frequent turnover of championship teams was not observed in all conferences. Potential implications for these findings and their impact on college football are discussed.
Keywords: NCAA; Bowl Championship Series; intercollegiate athletics; college football; competitive balance; Herfindahl- Hirschman Index; bowl games; college conferences